Does audit quality affect firms' investment efficiency?. Issue 10 (3rd October 2018) - Boubaker, Sabri; Houcine, Asma; Ftiti, Zied; Masri, Hatem
Abstract: This study investigates the effect of audit quality on firm investment efficiency for 125 French-listed companies over 2008–2015. It uses parametric and non-parametric measures of firm investment efficiency, based on residuals extracted from the investment efficiency model and the data envelopment analysis (DEA) approach, respectively, to assess whether audit quality improves investment inefficiency. It analyses this relationship after distinguishing between firms that under-invest and those that over-invest. The results show that investment inefficiency decreases with audit quality. Specifically, auditor knowledge leads to less investment in firms prone to over-investment and more investment in firms prone to under-investment. This relationship appears to be independent of a firm's financial reporting quality, which indicates that auditors provide value-added services that impact the investment decisions of firm managers, separately from the quality of accounting information.